2014
DOI: 10.1113/expphysiol.2014.078840
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of corticospinal changes during and after high‐intensity quadriceps exercise

Abstract: New FindingsOur results show that single-joint knee-extensor isometric exercise induces late supraspinal fatigue with increased intracortical inhibition, both of which recover quickly after task failure, and unchanged corticospinal excitability. This indicates that fatigue-induced corticospinal changes are muscle and/or limb specific and reinforces the need to measure corticospinal changes within seconds after task failure to avoid their underestimation. This study tested the hypothesis that during fatiguing q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
89
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(104 citation statements)
references
References 44 publications
(138 reference statements)
12
89
2
1
Order By: Relevance
“…This 5–10 min recovery period was notably shorter than those reported in previous studies with comparable neuromuscular protocols [20 min (Millet et al., ), 30 min (Saugy et al., ), 55–120 min (Temesi et al., )]. However, neuromuscular recovery might have occurred in this time lapse and central (Gruet et al., ) and peripheral (Froyd et al., ) mechanisms recovery might be expected.…”
Section: Discussionmentioning
confidence: 56%
“…This 5–10 min recovery period was notably shorter than those reported in previous studies with comparable neuromuscular protocols [20 min (Millet et al., ), 30 min (Saugy et al., ), 55–120 min (Temesi et al., )]. However, neuromuscular recovery might have occurred in this time lapse and central (Gruet et al., ) and peripheral (Froyd et al., ) mechanisms recovery might be expected.…”
Section: Discussionmentioning
confidence: 56%
“…Although we do not have any data on either central or peripheral factors explaining our results, the observed changes in maximal torque and RTD in this study could be attributed to both central and peripheral factors, with a particular emphasis on the latter. This issue requires further investigation utilizing such techniques as transcranial magnetic stimulation and peripheral nerve stimulation 6, 7 .…”
Section: Discussionmentioning
confidence: 99%
“…It is often reported that trail running and mountain ultra-marathon races induce muscle damage in leg muscles, demonstrating as strength loss, occurrence of delayed onset muscle soreness (DOMS), and increased plasma creatine kinase (CK) activity, which could take several days to recover 25 . While exercise-induced strength loss can originate at central and/or peripheral levels 6 , central changes recover quickly from a fatigued state 4, 7, 8 (as early as within few seconds 7 ), and do not last for a few days even after performing >30 h of mountain ultra-marathon 4 . Thus, it is suggested that prolonged strength loss lasting for several days, as well as increased DOMS and CK that usually peak 1–3 days post-exercise, can be mainly attributed to muscle damage (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Participants completed a standardised isometric warm‐up (Gruet et al . ), before a baseline neuromuscular function assessment. After 5 min of passive rest, participants completed an intermittent isometric fatiguing task to failure at an intensity relative to their critical intensity (+10 or −10%).…”
Section: Methodsmentioning
confidence: 99%